2001
DOI: 10.1037/0893-164x.15.3.227
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol involvement and dysphoria: A longitudinal examination of gender differences from late adolescence to adulthood.

Abstract: Although numerous investigations have examined the relations between alcoholism and depression, differing results have emerged. Major limitations in existing work are that it uses clinical samples and is cross-sectional in nature. Using prospective data from a community sample assessed during 3 developmental periods (late adolescence, young adulthood, and adulthood), these complex relations were examined with structural equation modeling. Results show distinct gender differences between alcohol involvement and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 38 publications
2
27
1
1
Order By: Relevance
“…Findings from several longitudinal studies suggest a transactional association between heavy alcohol use and depression in which each condition prospectively exacerbates the other (Gilman and Abraham, 2001;Locke and Newcomb, 2001;Marmorstein, 2009;Windle and Miller, 1990). Although a handful of researchers have found no evidence of a prospective association between the two (Fleming et al, 2008), with few exceptions (Kaplow et al, 2001) this research has not considered other forms of psychological distress, particularly anxiety, which is also known to be associated with hazardous drinking (Kushner et al, 1999;Regier et al, 1998).…”
Section: Alcohol Use and Depressionmentioning
confidence: 99%
“…Findings from several longitudinal studies suggest a transactional association between heavy alcohol use and depression in which each condition prospectively exacerbates the other (Gilman and Abraham, 2001;Locke and Newcomb, 2001;Marmorstein, 2009;Windle and Miller, 1990). Although a handful of researchers have found no evidence of a prospective association between the two (Fleming et al, 2008), with few exceptions (Kaplow et al, 2001) this research has not considered other forms of psychological distress, particularly anxiety, which is also known to be associated with hazardous drinking (Kushner et al, 1999;Regier et al, 1998).…”
Section: Alcohol Use and Depressionmentioning
confidence: 99%
“…While exceptions do exist (Hussong & Hicks, 2003), several longitudinal studies have found evidence indicating that childhood depressive symptoms in boys are associated with increased alcohol use (Costello et al, 1999;Henry et al, 1993;Kaplow et al, 2001;Pardini et al, 2004), and a higher rate of substance use disorders (Sung et al, 2004) during adolescence. In addition, depression and dysphoria among male adolescents have been related to increased alcohol involvement in early adulthood, even after controlling for initial levels of substance using behaviors (Locke & Newcomb, 2001). A potential confound in some of these studies is that commonly used measures of childhood depression often include items related to conduct problems (Weiss et al, 1991), which may account for the positive relation between depression and substance use (Kumpulainen & Roine, 2002).…”
Section: Internalizing Problems and Alcohol Use Disordersmentioning
confidence: 99%
“…Preclinical models demonstrate promise for MAO-A inhibitors to reduce ethanol consumption (60,61), and MAO-A inhibitors also have the potential to protect mitochondria against ethanol-induced toxicity in multiple organs (4) and to treat the mood symptoms that are often observed in AD (49,50). However, there have been no investigations of MAO-A inhibitors as a pharmacotherapy for AD in humans.…”
Section: Discussionmentioning
confidence: 99%
“…A stepwise regression was applied that included three predictor variables: the visual analogue score for depressed mood, group (AD vs. healthy, because it is well established that depressed mood is associated with alcohol dependence) (49,50), and angry-hostility, a personality facet score (from the NEO Personality Inventory-Revised) previously associated with MAO-A V T (14,15). All factors were significant (multivariate analysis of covariance, effect of depressed mood, F 2,26 = 4.88, p = .02; effect of group, F 2,26 = 5.38, p = .01; effect of angry-hostility, F 2,26 = 6.02, p = .007) and were related to the dependent variables in a manner consistent with greater MAO-A V T when depressed mood is elevated and lower MAO-A V T when angry-hostility is present, see Figure 3.…”
Section: Relationship Between Mao-a V T and Other Clinical Featuresmentioning
confidence: 99%